EFFICIENCY OF CASH TURNOVER, INVENTORY, AND RECEIVABLES: THE SECRETS BEHIND THE PROFITABILITY LEVEL OF FOOD AND BEVERAGE COMPANIES - Mochamad Arif; Zumrotun Nafiah; Frida Widyawati Triasningrum (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
This study aims to analyze the effect of cash turnover, inventory turnover, and receivables turnover on profitability in manufacturing companies within the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. Profitability reflects a company's ability to generate profits through the effective management of resources and working capital. In this study, profitability is measured using the Return on Assets (ROA) ratio, which indicates how efficiently assets are utilized to generate earnings. The research data were obtained from the annual financial reports of companies listed on the IDX. The population consisted of 46 manufacturing companies, and by applying a purposive sampling technique, 12 companies were selected as samples over a three-year observation period, resulting in 36 total data observations. This study employs a quantitative associative approach, and the data were analyzed using multiple linear regression with the SPSS software. The results show that cash turnover has no significant effect on profitability, indicating that fluctuations in cash do not necessarily impact company profits. In contrast, inventory turnover has a positive and significant effect on profitability, implying that faster inventory conversion into sales leads to higher profits. Meanwhile, receivables turnover also has a significant effect on profitability, demonstrating that effective receivables management contributes to increased profitability. Simultaneously, the three independent variables—cash turnover, inventory turnover, and receivables turnover—affect the profitability of manufacturing companies. These findings highlight the importance of effective working capital management in enhancing financial performance. Efficient management of cash, inventory, and receivables helps maintain liquidity and accelerate the operating cycle, which ultimately boosts profitability. This study is expected to provide valuable insights for manufacturing companies to optimize their working capital management and for investors to assess corporate financial performance. Moreover, it serves as an academic reference for future research by suggesting the inclusion of additional variables such as firm size or liquidity.